Tecnologia educacional para pacientes em diálise peritoneal: construção e validação - Zerbinato, Viviany Abreu de Souza (2019)
Introduction: Peritoneal dialysis represents a dialysis therapy performed at home, providing the patient with total control and autonomy, through therapy management. However, for adequate training, the nurse promotes training and guidance to the patient and family / caregivers in order to transmit knowledge related to the dialysis technique, catheter care, food and medications, prevention of infections and other essential care to adapt the patient to therapy. The nurse, therefore, is the professional with the greatest bond with the patient and plays a fundamental role in this educational process, as he is responsible for welcoming, sharing knowledge and therapeutic monitoring. In this context, educational technologies are necessary as learning tools for actions aimed at self-care. Objectives: To develop and validate an instrument to support training for the care of chronic renal patients undergoing peritoneal dialysis therapy. Method: Methodological study developed in three stages: 1) survey of the profile of PD patients and their needs; 2) elaboration of educational technology; and 3) validation of educational technology. The content of the almanac was elaborated from a literature review and focus group with patients. To validate the content of the almanac, judges were invited, selected by the “snowball” technique and indication of specialists from the researcher's relational universe. The evaluation criterion used was an agreement level greater than 80%, analyzed using the Content Validity Index (CVI) and judgments according to the three-point Likert scale, being: “inadequate = 1”, “needs adjustments = 2”, “Adequate = 3”. Results: During the first round of validation, the almanac reached a global CVI of 0.86, therefore valid content, with all suggestions made by the judges accepted and adjusted material. This work allowed the development of three products: two scientific articles related to the theme and a technical production in the form of an almanac. The Almanac of Peritoneal Dialysis presents essential care for the safe therapy of a patient undergoing home dialysis, treating subjects of great relevance through simple, accessible language and playful content for greater interaction with the target audience. This almanac was composed of 11 topics: "The Origin of Peritoneal Dialysis", "From diagnosis to adaptation ...", "Care with PD catheter", "Physical Activity", "Travel and Plans", "Food", "Medication”,“ Dialysis environment ”,“ Sexuality and married life ”,“ Avoiding complications in PD and intercurrences ”. Conclusion: An educational technology for patients undergoing peritoneal dialysis therapy was built and validated. It is believed that the almanac will act as a learning facilitator for patients and caregivers, representing health professionals as a tool didactics of great importance in specialized assistance.